(untitled) (Praxis Educativa, 2022)
Postgraduate programs in education offered by Higher Education Institutions (HEI) in Mexico, even those oriented towards research, face the problem of low terminal efficiency, in terms of indicators is translated into the low number of graduates; problem that is the product of the interweaving of multiple factors and conditions, one of the most common that as an Academic Body we found in our studies, is the way in which the processes of training for research are oriented. In this article we share the process, findings and propositional elements of a study in which we document the training processes related to this task, particularly the experiences and knowledge about the methodology and didactics of research that research teachers of the Instituto Superior de Ciencias de la Educación del Estado de México (ISCEEM) and other graduate institutions have accumulated in their trajectory as thesis tutors.